Potential and Possibility of Developing Guwahati as a Primate City in North East India. Issue 1 (January 2015) - Sahay, Avijit; Roy, Nikhil; Kumar, Abhimanyu
Despite being well endowed with natural resources, north eastern frontier of India is considered to be one of economically laggard regions. Absence of adequate infrastructure, coupled with a lack of any economically vibrant urban centre, has impeded the economic growth and development of the North East India. The paper is an attempt to deliberate on the need of establishing a Primate city in the region which can attract investments and industries. Such a city, it is argued, will create jobs, increase economic growth, and stem the flow of ever increasing out migration from the region to major urban centres of the rest of India. Demographic, industrial and migration data of major cities of North East India will be evaluated to ascertain the suitability of Guwahati as such a future mega city of the region.